ANALISIS KUALITAS BAHAN BAKU DAN PROSES PRODUKSI TERHADAP KUALITAS PRODUK PADA PT SUPER BOX INDUSTRIES - Wahyuni, Gita; Efriyenti, Dian (SCIENTIA JOURNAL, 2021)
At the time of manufacturing a product, there are constraints on the use of raw materials such as when using high glue, the water content tends to be high so that the impact on the cardboard can become soft and vice versa. Therefore, companies must always optimize the quality of raw materials and production processes. The purpose of this study was to determine the quality of raw materials and production processes that affect product quality at PT Super Box Industries. In this study there were 100 employee populations and the sample used in this study amounted to 71 employees. The sampling technique used was saturated sampling method. The analysis in this research is descriptive analysis, classical assumptions, and multiple linear regression analysis. The results of this study indicate that partially the quality of raw materials has a significant effect on product quality, partially the production process has a significant effect on product quality and simultaneously the quality of raw materials and production processes has a significant effect on the level of product quality at PT Super Box Industrie.